P829 The Burden of Colorectal Cancer in Patients with Ulcerative Colitis – Incidence and Risk factors from a Population-based Inception Cohort from Veszprem county, Western Hungary, from 1977–2020. (30th January 2023) - Wetwittayakhlang, P; Golovics, P; Gonczi, L; Khoury, A; Kurti, Z; Pandur, T; David, G; Erdelyi, Z; Szita, I; Lakatos, L; Lakatos, P L
Abstract: Background: Limited data are available on the incidence and risk of colorectal cancer (CRC) in ulcerative colitis (UC) from population-based studies in Eastern Europe. We aimed to identify the long-term incidence trends and predictors of CRC in a prospective population-based inception cohort from Veszprem, Western Hungary. Methods: Patient inclusion for the inception cohort was between January 1, 1977 and December 31, 2018, and follow-up ended December 31, 2020. The risk of CRC was estimated using standardized incidence ratios (SIRs). Age-and gender-specific CRC rates of the background population were derived from the National Cancer Registry. Results: A total of 1, 370 incident UC patients were included [male:51.2%, median age at diagnosis:37years). During a median follow-up of 17 years(IQR9-24), CRC was diagnosed in 41 UC patients(2.99%), equaling 1.76/1000 person-year(py).Median age at CRC diagnosis was 59(IQR:50.0-67.5) years. Overall SIR of CRC was 2.02(CI95%:10.1-12.1). SIRs were higher in extensive colitis (SIR:3.77, CI95%:2.41-5.91). The cumulative probability of CRC at 10-, 20 and 30 years was 0.9% (95%CI0.6-1.2), 3.5%(95%CI2.8-4.2), and 6.5%(95%CI5.4-7.6), and there was no difference in the risk of CRC over different decades of UC diagnosis in a Kaplan Meier analysis(Log-rank=0.693). In multivariate analyses, co-existing PSC(HR4.19;95%CI1.72-10.20), colonic dysplasia(3.42;95%CI1.04-11.26), and extensive colitis (HR2.15;95%CI1.29-3.60) were identified as a significant predictor for CRC. Conclusion: We report an increased CRC risk in UC patients with a standardized incidence ratio of approximately 2 folds, with a stable CRC risk over four decades. Disease extent, co-existing PSC and dysplasia were identified as predictors of CRC.